Immunomodulatory Role of Tenascin-C in Myocarditis and Inflammatory Cardiomyopathy - Tajiri, Kazuko; Yonebayashi, Saori; Li, Siqi; Ieda, Masaki (Frontiers in Immunology, 2021)
Accumulating evidence suggests that the breakdown of immune tolerance plays an important role in the development of myocarditis triggered by cardiotropic microbial infections. Genetic deletion of immune checkpoint molecules that are crucial for maintaining self-tolerance causes spontaneous myocarditis in mice, and cancer treatment with immune checkpoint inhibitors can induce myocarditis in humans. These results suggest that the loss of immune tolerance results in myocarditis. The tissue microenvironment influences the local immune dysregulation in autoimmunity. Recently, tenascin-C (TN-C) has been found to play a role as a local regulator of inflammation through various molecular mechanisms. TN-C is a nonstructural extracellular matrix glycoprotein expressed in the heart during early embryonic development, as well as during tissue injury or active tissue remodeling, in a spatiotemporally restricted manner. In a mouse model of autoimmune myocarditis, TN-C was detectable before inflammatory cell infiltration and myocytolysis became histologically evident; it was strongly expressed during active inflammation and disappeared with healing. TN-C activates dendritic cells to generate pathogenic autoreactive T cells and forms an important link between innate and acquired immunity.